(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Electric machine technologies play a critical role in modern industrial, transportation, and renewable energy systems. As global efforts toward decarbonization and energy efficiency intensify, electric machines are increasingly replacing traditional mechanical and combustion-based systems. This paper explores both the limitations and opportunities associated with electric machine technologies. Key limitations include material constraints (such as rare-earth magnets), thermal management challenges, cost-effectiveness, and efficiency at variable loads. Additionally, integration with power electronics and the need for advanced control systems present engineering hurdles. On the opportunity side, recent advancements in wide bandgap semiconductors, additive manufacturing, and smart materials offer promising avenues for performance enhancement. Emerging designs like axial flux machines, switched reluctance motors, and superconducting machines are opening new frontiers in power density and efficiency. The transition to electric mobility and distributed energy systems further accelerates innovation and demand for robust, sustainable electric machine solutions. This study aims to provide a balanced overview, highlighting areas of technological progress while identifying key challenges that must be addressed to fully realize the potential of next-generation electric machines.